IL-4 Induces Metallothionein 3- and SLC30A4-Dependent Increase in Intracellular Zn(2+) that Promotes Pathogen Persistence in Macrophages - Vignesh, Kavitha Subramanian (Cell Rep, 2016)
Alternative activation of macrophages promotes wound healing but weakens antimicrobial defenses against intracellular pathogens. The mechanisms that suppress macrophage function to create a favorable environment for pathogen growth remain elusive. We show that interleukin (IL)-4 triggers a metallothionein 3 (MT3)- and Zn exporter SLC30A4- dependent increase in the labile Zn(2+) stores in macrophages and that intracellular pathogens can exploit this increase in Zn to survive. IL-4 regulates this pathway by shuttling extracellular Zn into macrophages and by activating cathepsins that act on MT3 to release bound Zn. We show that IL-4 can modulate Zn homeostasis in both human monocytes and mice. In vivo, MT3 can repress macrophage function in an M2-polarizing environment to promote pathogen persistence. Thus, MT3 and SLC30A4 dictate the size of the labile Zn(2+) pool and promote the survival of a prototypical intracellular pathogen in M2 macrophages.